Strengthening Aging Research Through Dissemination and Implementation Science Methods. - Bobitt, Julie; Jarrott, Shannon E (Gerontologist, 2023)
An introduction to the journal is presented in which the guest editors discuss the growing use of implementation science (IS), or of strategies to adopt and integrate evidence-based health interventions into routine practice, in gerontology and geriatric research as of 2023.